Building Inclusive Narratives: Methodological Strategies for Creating Stories in Teacher Trainingand University Outreach - Solís Sánchez, María Gabriela (2024)
The presented methodological and interdisciplinary experience implies a synergy between teaching and university extension at the National University of Costa Rica. The main purpose is to develop learning experiences that foster collaboration, recognition of diversity, and disciplinary encounters in initial teacher education. A total of 48 fourth-level students in Special Education and third-level students in Preschool Education, organized into 12 mixed groups of four individuals each, participated in this initiative along with academic-extensionists from the project "Literacy: A perspective for the construction of inclusive reading environments". The pedagogical proposal is based on the methodology systematized by teacher Oscar Jara, but it is adapted and enriched through three key moments: the initial experience of training in "creating inclusive stories", the interdisciplinary itinerary, and the resulting reflections. During six in-person pedagogical meetings at UNA, aspects of language development were addressed from an interdisciplinary perspective, with an emphasis on Universal Design for Learning (UDL). The result was the creation of 12 inclusive stories, developed according to the principles of UDL. Through workshop dynamics and reflections, the feelings and thoughts of the participants were reconstructed, thus enriching the initial teacher training experience with an interdisciplinary approach. It is worth noting that this experience enhances the formation of the professional profile, promoting reflective skills, respect, dialogue, and joint construction, in line with regulations on inclusive education and early childhood. In conclusion, this initiative demonstrates how university teaching can promote the training of future professionals committed to inclusion and respect for diversity, through interdisciplinary approaches that foster a deeper and more coherent pedagogical practice with the current demands of the educational field.